Bidirectional Mast Cell–Eosinophil Interactions in Inflammatory Disorders and Cancer - Galdiero, Maria Rosaria; Varricchi, Gilda; Seaf, Mansour; Marone, Giancarlo; Levi-Schaffer, Francesca; Marone, Gianni (Frontiers in Medicine, 2017)
Human mast cells (MCs) and eosinophils were first described and named by Paul Ehrlich. These cells have distinct myeloid progenitors and differ morphologically, ultrastructurally, immunologically, biochemically and pharmacologically. However, MCs and eosinophils play a pivotal role in several allergic disorders. In addition, these cells are involved in autoimmune disorders, cardiovascular diseases and cancer. MCs are distributed throughout all normal human tissues, whereas eosinophils are present only in gastrointestinal tract, secondary lymphoid tissues, and adipose tissue, thymus, mammary gland and uterus. However, in allergic disorders MCs and eosinophils can form the “allergic effector unit”. Moreover, in several tumors, MCs and eosinophils can be found in close proximity. Therefore, it is likely that MCs have the capacity to modulate eosinophil functions and vice versa. For example, IL-5, stem cell factor (SCF), histamine, platelet activating factor (PAF), prostaglandin D2 (PGD2), cysteinyl leukotrienes and vascular endothelial growth factors (VEGFs), produced by activated MCs, can modulate eosinophil functions through the engagement of specific receptors. On the other side, eosinophil cationic proteins such as eosinophil cationic protein (ECP) and major basic protein (MPB), nerve growth factor (NGF) and VEGFs released by activated eosinophils can modulate mast cell functions. These bidirectional interactions between MCs and eosinophils might be relevant not only in allergic diseases, but also in several inflammatory and neoplastic disorders.